2015
DOI: 10.1108/s0147-912120140000041015
|View full text |Cite
|
Sign up to set email alerts
|

Gender Complementarities in the Labor Market

Abstract: In this paper we provide estimates of the short-run elasticity of substitution between male and female workers, using data from Italian provinces for the period 1993-2006. We adopt a production function approach similar to Card and Lemieux (2001a) and Acemoglu, Autor, and Lyle (2004). Our identification strategy relies on a natural experiment. In 2000, the Italian parliament passed a law to abolish compulsory military service. The reform was implemented through a gradual reduction in the number of draftees; co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In a neoclassical theory of supply and demand, these results can be interpreted as showing that men and women in an aggregate production function are not perfect substitutes. Using a similar framework to examine the abolition of compulsory military service and sex ratios at birth in Italy as factors explaining the relative supply of male and female workers, De Giorgi et al (2015) also found evidence of imperfect substitutability with an elasticity of approximately 1. Freire (2011) analyzed the effects of the relative supply of men and women on wages in Brazil, examining rural-urban migration as the exogenous factor that produces changes in urban economies, and found that greater female participation increased the wage gap between men and women, with an estimated elasticity of substitution of 1.78.…”
Section: Introductionmentioning
confidence: 99%
“…In a neoclassical theory of supply and demand, these results can be interpreted as showing that men and women in an aggregate production function are not perfect substitutes. Using a similar framework to examine the abolition of compulsory military service and sex ratios at birth in Italy as factors explaining the relative supply of male and female workers, De Giorgi et al (2015) also found evidence of imperfect substitutability with an elasticity of approximately 1. Freire (2011) analyzed the effects of the relative supply of men and women on wages in Brazil, examining rural-urban migration as the exogenous factor that produces changes in urban economies, and found that greater female participation increased the wage gap between men and women, with an estimated elasticity of substitution of 1.78.…”
Section: Introductionmentioning
confidence: 99%